2019
DOI: 10.1021/acschemneuro.9b00429
|View full text |Cite
|
Sign up to set email alerts
|

Do Toxic Synthetic Cannabinoid Receptor Agonists Have Signature in Vitro Activity Profiles? A Case Study of AMB-FUBINACA

Abstract: Recreational consumption of synthetic cannabinoid receptor agonists (SCRAs) is a growing crisis in public health in many parts of the world. AMB-FUBINACA is a member of this class of drugs and is responsible for a large proportion of SCRA-related toxicity both in New Zealand and internationally. Strikingly, little is currently known about the mechanisms by which SCRAs exert toxic effects or whether their activity through the CB 1 cannabinoid receptor (the mediator of cannabinoid-related psychoactivity) is suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
67
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 60 publications
(126 reference statements)
12
67
2
Order By: Relevance
“…Canonically, β‐arrestins are known to be involved in GPCR internalization, however recent reports suggest that arrestins may also be responsible for certain G protein‐independent responses . The latter finding has prompted the notion that SCRA‐mediated activation of β‐arrestin ‐1 and ‐2 may play an important role in SCRA toxicity . Notwithstanding, the exact mechanism(s) of observed SCRA toxicity remains largely elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Canonically, β‐arrestins are known to be involved in GPCR internalization, however recent reports suggest that arrestins may also be responsible for certain G protein‐independent responses . The latter finding has prompted the notion that SCRA‐mediated activation of β‐arrestin ‐1 and ‐2 may play an important role in SCRA toxicity . Notwithstanding, the exact mechanism(s) of observed SCRA toxicity remains largely elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic cannabinoids do not contain cannabidiol (the main neuro-protective compound found in natural cannabis which predominantly acts on CB2 receptors) and this may also be related to the increased toxicity observed with these compounds compared with natural cannabis. 95,96 Synthetic cannabinoids have a greater potency and binding affinity than d9-THC at the cannabinoid receptors. They are full agonists compared with the partial agonist properties of d9-THC, with potency of 10-200 times greater than that of d9-THC.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…These differences likely underpin the emerging greater incidence of major psychiatric complications and other adverse effects compared with traditional cannabis. [96][97][98][99] A self-reported survey of 80,000 illicit substance users revealed that those who used synthetic cannabinoids were 30 times more likely to end up in an emergency department than users of traditional cannabis. 79 Harms and adverse effects There is currently no evidence for any therapeutic potential of synthetic cannabinoids with overwhelming reports of mild to severe adverse effects.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism(s) through which SCRAs exert different behavioral and physiological effects remains unclear, and which pathways modulated by CB1 activation mediate the specific pharmacological effects of SCRAs is also unknown. Similarly, the question of whether these pathways are activated in a quantitatively or qualitatively similar way by SCRAs and THC is only beginning to be addressed . Finally, the question of whether SCRA activity at noncannabinoid receptors is also important for their pharmacological effects is very much open .…”
Section: Introductionmentioning
confidence: 99%